A cohesion loss model for determining residual strength of intact rocks. (July 2019) - Peng, Jun; Cai, Ming
Abstract: Residual strength of rock is required in stability evaluation of underground excavations such as tunnels and caverns. Accurate determination of residual strength of rock can facilitate cost-effective design of these underground structures. This study investigates the methods for determining residual strength of intact rocks. Firstly, previous methods for determining residual strength of intact rocks are examined from a literature review, and a new method, which uses the concept of cohesion loss, is proposed. The proposed cohesion loss model is based on the framework of the widely-used Hoek–Brown (H–B) strength model. It is simple and contains only one parameter that controls the nonlinearity of the residual strength envelope. The cohesion loss model is validated using two sets of test data and the results show that the model can represent residual strength envelopes of intact rocks satisfactorily. Finally, the model parameter is studied by examining a large amount of test data collected from previous publications. It is found that the model parameter varies for different rock types and shows a decreasing trend as the rock strength increases. Overall, the results in this study show that the proposed model can capture the residual strength of intact rocks.